Long-term care insurance and the future of healthy aging in China - Chen, Simiao; Li, Linye; Jiao, Lirui; Wang, Chen (Nature aging, 2023)
China faces urgent challenges associated with population aging. In this Comment, we summarize China’s adoption of long-term care insurance and underscore its importance for social and economic wellbeing. We provide recommendations for a future of sustainable and healthy aging in China.
Gesehen am 28.06.2024